Therapeutic Ureteral Occlusion with Ifabond Cyanoacrylate Glue: An Interesting Solution. Issue 3 (July 2017) - Oderda, Marco; Lacquaniti, Sergio; Fraire, Flavio; Antolini, Jacopo; Camilli, Marco; Mandras, Roberto; Puccetti, Luca; Varvello, Francesco; Fasolis, Giuseppe
Objective: The aim of this study was to present a novel approach for complete and permanent ureteral occlusion using a percutaneous injection of Ifabond cyanoacrylate glue. Methods: We describe in detail all the steps of our surgery, performed on a 79-year-old patient with urinary leakage from ureteral stump following radical cystectomy. N-hexyl-cyanoacrylate glue (Ifabond) was used to occlude the distal ureter and solve the leakage. Results: Our approach was successful, sparing our already frail patient further surgical procedures. Six months pyelography confirmed the complete ureteral blockage with absence of extravasation. Conclusions: In complicated scenarios with urinary leakages and frail patients, synthetic glues such as Ifabond might represent an interesting therapeutic option to solve the fistulas, leading to durable success with a minimally invasive approach.